2007
DOI: 10.1680/geot.2007.57.6.537
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional slope stability analysis by elasto-plastic finite elements

Abstract: Slope stability analysis is one of the oldest applications in geotechnical engineering, yet it remains one of the most active areas of study in both research and practice. The vast majority of slope stability analyses are performed in two dimensions under the assumption of plane strain conditions. Even when two-dimensional (2D) conditions are not appropriate, three-dimensional (3D) analysis is rarely performed. There are a number of reasons for this. The majority of work on this subject strongly suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
118
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 313 publications
(137 citation statements)
references
References 36 publications
4
118
1
2
Order By: Relevance
“…Despite the availability of threedimensional computer programs for analyzing deformation and stability in slopes, the calculations require many assumptions with regard to lateral forces, the initial stress distribution and other criteria of the critical slip surfaces which is sometimes lacking (Gri‹ths and Marquez, 2007;Loehr et al, 2004;Ugai and Leshchinsky, 1995;Wei et al, 2009). On the other hand, a two-dimensional analysis for the most critical cross-section will always lead to a conservative factor of safety; therefore, a three-dimensional analysis is not commonly employed for slope stability analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of threedimensional computer programs for analyzing deformation and stability in slopes, the calculations require many assumptions with regard to lateral forces, the initial stress distribution and other criteria of the critical slip surfaces which is sometimes lacking (Gri‹ths and Marquez, 2007;Loehr et al, 2004;Ugai and Leshchinsky, 1995;Wei et al, 2009). On the other hand, a two-dimensional analysis for the most critical cross-section will always lead to a conservative factor of safety; therefore, a three-dimensional analysis is not commonly employed for slope stability analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The factor of safety in three dimension was always higher than in two dimension owing to side support, but tended to the plane strain solution for length ratios of the order of L/H > 10. It should be mentioned that Griffiths & Marquez (2007) used a mesh density similar to that shown in figure 3 but demonstrated that while finer meshes always gave slightly lower factors of safety than the coarser mesh, the difference never exceeded 2 per cent. …”
Section: Deterministic Analysesmentioning
confidence: 99%
“…First, a conservative result will only be obtained if the most 'pessimistic' plane within a three-dimensional problem is selected for two-dimensional analysis. Griffiths & Marquez (2008) clearly showed planes within a three-dimensional slope that gave higher (unconservative) two-dimensional factors of safety than that of the full three-dimensional problem. In a slope that contains layering and strength variability in the out-of-plane direction, the choice of a two-dimensional pessimistic section may not be intuitively obvious.…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic requires special attention from engineers with regard to the low shear strength of the weak layer, which has an adverse influence on the performance of slopes. Varying methodologies have been employed to estimate the static stability of slopes with a thin layer, including the limit equilibrium method (Fredlund and Krahn [1]), the upper-bound solution method (Huang and Song [2]), and finite element analysis (Griffiths and Marquez [3]; Ho [4]). However, few studies have focused on the seismic stability of nonhomogeneous slopes.…”
Section: Introductionmentioning
confidence: 99%